Helping the Front: Help of the Local Population in the Battle of Kursk. Part 1 - V. P. Gridnev (Управленческое консультирование)
The relevance of this topic is due to the fact that in the face of threats and challenges, the Russian Federation and its Armed Forces face the task of ensuring the national security of the country, educating the young generation and society as a whole in the spirit of patriotism. One of the tools to achieve this strategic goal is the historical military experience of our Great country. Military history and the history of wars and military art indicate that the Battle of Kursk, in its results and the significance of the victory of the Soviet troops near Moscow and Stalingrad, became a powerful stage on the way to the victory of the Soviet Union over fascist Germany. If the Battle of Stalingrad foreshadowed the decline of the German fascist army, the battle of Kursk put it before a catastrophe. A great role in achieving victory was played by the unity of the front and rear, all-round assistance of the local population. In this article, extensive archival and documentary materials, memoirs of participants in the battle, newspaper materials reveal comprehensive assistance to the population of the front-line areas of the army in the field. The author emphasizes in the Battle of Kursk organizational activity, the role and place of government, military administration.